2010
DOI: 10.1111/j.1399-6576.2009.02112.x
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time ultrasound‐guided spinal anesthesia in patients with a challenging spinal anatomy: two case reports

Abstract: Spinal anesthesia may be challenging in patients with poorly palpable surface landmarks or abnormal spinal anatomy. Pre-procedural ultrasound imaging of the lumbar spine can help by providing additional anatomical information, thus permitting a more accurate estimation of the appropriate needle insertion site and trajectory. However, actual needle insertion in the pre-puncture ultrasound-assisted technique remains a 'blind' procedure. We describe two patients with an abnormal spinal anatomy in whom ultrasound-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 14 publications
(14 reference statements)
0
39
0
Order By: Relevance
“…Some studies have shown increased success rates when ultrasound is used in patients with obscured landmarks or difficult anatomy [1921]. However, this might involve teaching both SpA and the use of an ultrasound machine to trainees at the same time, which may be an even bigger challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown increased success rates when ultrasound is used in patients with obscured landmarks or difficult anatomy [1921]. However, this might involve teaching both SpA and the use of an ultrasound machine to trainees at the same time, which may be an even bigger challenge.…”
Section: Discussionmentioning
confidence: 99%
“…In particular this technique avoids the potential for error in the process of having to “remember” the degree of cephalad to caudad and lateral to medial angulation required after pre-puncture skin marking. To date we can find only one case report [10] and one report of a series of 10 patients [11] where the technique of real time ultrasound guided spinal anaesthesia has been employed. The aim of this single center prospective observational study was to investigate the feasibility of performing a systematic method for real-time ultrasound guided paramedian access to the subarachnoid space with the spinal needle inserted in the plane (in-plane) of the ultrasound beam by a single operator.…”
Section: Introductionmentioning
confidence: 99%
“…31 Real-time ultrasound-guided LP is most often performed using a longitudinal (in-plane), paramedian approach. [31][32][33][34][35][36][37] One prospective study using a conventional curvilinear transducer and a longitudinal paramedian approach demonstrated a 97% success rate with a median of 3 needle passes (interquartile range 1-6). 34 Although small studies describing real-time ultrasound guidance appear promising, lumbar spine mapping to mark the needle insertion site is currently the most common technique with the largest body of supporting evidence.…”
Section: Literature Reviewmentioning
confidence: 99%